Síndrome antifosfolípide e trombocitopenia na infância - Turini, Roberta Bittencourt F.; Chechia, Taiana Emílio; Fernandes, Tadeu Augusto; Bom, Ana Paula K. P.; Bandeira, Márcia [UNESP] (My University, 2012)
Objective: To report the case of a child diagnosed with antiphospholipid syndrome associated with severe thrombocytopenia, and to review the literature on the subject. Case description: Child aged nine years and eight months old with severe thrombocytopenia associated with a positive anticardiolipin antibody. Data were collected by clinical history, physical examination, and laboratorial exams. Diagnosis was confirmed according to criteria established for the antiophospholipid syndrome, associated with the presence of the most common manifestations of the syndrome in children: livedo reticularis and thrombocytopenia. Comments: The antiphospholipid syndrome is an uncommon pediatric disease, and clinical manifestations such as decreased platelet number should be considered.
Antiphospholipid syndrome and thrombocytopenia in childhood
Keywords: Antiphospholipid syndrome; Livedo reticularis; Thrombocytopenia; beta2 glycoprotein 1 antibody; cardiolipin antibody; hemoglobin; hydroxychloroquine; immunoglobulin G antibody; immunoglobulin M antibody; lupus anticoagulant; prednisone; antiphospholipid syndrome; case report; child; disease association; disease severity; drug dose reduction; ecchymosis; epistaxis; female; gingiva bleeding; hemoglobin blood level; human; idiopathic thrombocytopenic purpura; livedo reticularis; medical history; physical examination; school child; thrombocyte count; thrombocytopenia